Mutagenesis-Based Characterization and Improvement of a Novel Inclusion Body Tag - Jong, Wouter S. P.; ten Hagen-Jongman, Corinne M.; Vikström, David; Dontje, Wendy; Abdallah, Abdallah M.; de Gier, Jan-Willem; Bitter, Wilbert; Luirink, Joen (Frontiers in Bioengineering and Biotechnology, 2020)
Whereas bacterial inclusion bodies (IBs) for long were regarded as undesirable aggregates emerging during recombinant protein production, they currently receive attention as promising nanoparticulate biomaterials with diverse applications in biotechnology and biomedicine. We previously identified ssTorA, a signal sequence that normally directs protein export via the Tat pathway in E. coli, as a tag that induces the accumulation of fused proteins into IBs under overexpression conditions. Here, we used targeted mutagenesis to identify features and motifs being either critical or dispensable for IB formation. We found that IB formation is neither related to the function of ssTorA as a Tat-signal sequence nor is it a general feature of this family of signal sequences. IB formation was inhibited by co-overexpression of ssTorA binding chaperones TorD and DnaK and by amino acid substitutions that affect the propensity of ssTorA to form an α-helix. Systematic deletion experiments identified a minimal region of ssTorA required for IB formation in the center of the signal peptide. Unbiased genetic screening of a library of randomly mutagenized ssTorA sequences for reduced aggregation properties allowed us to pinpoint residues that are critical to sustain insoluble expression. Together, the data point to possible mechanisms for the aggregation of ssTorA fusions. Additionally, they led to the design of a tag with superior IB-formation properties compared to the original ssTorA sequence.